Big Data Analytics on data with the growing telecommunication market in a Distributed Computing Environment - Kartheek Pamarthi (North American Journal of Engineering Research, 2023)
The current global health situation (primarily as a result of Covid-19) has fostered a change in customer behaviour towards the use of telecommunications services, which has led to an increase in data traffic. As a result of this change, telecommunications operators have a golden opportunity to create new sources of revenue by utilising Big Data Analytics (BDA) solutions. In the process of establishing a BDA project, we encountered a number of obstacles, the most significant of which were the selection of the technological solution from among the vast array of tools that were already available, as well as the selection of the governance methodology that would be used to control both the project and the data. The vast majority of study materials that pertain to the telecommunications industry have not addressed the implementation of BDA projects from the beginning to the end. The goal of this study is to concentrate on a BDA telecommunications project, specifically the governance of the project, the architecture of the project, the governance of the data, and the team working on the BDA project. Utilisable BDA use cases are presented in the final section of this study. These use cases are presented in terms of applications that enable income generating and cost optimisation. It would appear that this effort will make it easier to implement BDA projects and will provide telecoms operators with the ability to have a better understanding of the fundamental components that need to be focused on.